Faith, Reason, and Character: A Systematic Review of Christian Educational Philosophy - Sadeva, Tia Aulia Putri; Parmiti, Desak Putu; Jampel, I Nyoman; Sanjaya, Dewa Bagus (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study analyzes the development of educational philosophy, focusing on the role of Christian philosophy of education in shaping a holistic, character-based educational paradigm compared to general educational philosophy. Methodology: The study uses a systematic literature review (SLR) method following the PRISMA 2020 protocol. Data were collected from Scopus, ERIC, Crossref, and Google Scholar, with publications from 2015 to 2025. The screening process yielded 22 eligible articles, which were analyzed using content analysis. Main Findings: General educational philosophy emphasizes rationality, empirical evidence, and humanism, fostering critical, adaptive learners. Christian philosophy integrates faith and reason, moral formation, and the teacher’s role as a spiritual and moral exemplar. Both share a holistic approach but differ in epistemological and axiological foundations, offering a balanced educational paradigm. Novelty/Originality of this study: This study provides a unique contribution by integrating Christian philosophy of education with general educational philosophy, promoting a balanced paradigm that nurtures both intellectual competence and spiritual, moral, and ethical development. It advances contemporary educational discourse by addressing the interplay between rationality and spirituality.